2011
DOI: 10.4197/met.22-3.4
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Al Asfar and Al Uyoun Evaporation Lakes Water Quality and the Potential of Its Reuse in Agriculture Activities, Al Hassa Area, KSA

Abstract: Studies of Al Asfar and Al Uyoun Evaporation Lakes…satellite image processing software (ERDAS Imagine) were used for the integration of the output parameters of this study and for visualization of their spatial distribution. The results indicate that surface water of Al Asfar and Al Uyoun lakes are characterized by relatively low salinity and then encourage to re-treat this considerable quantity of water and to reuse it in agricultural purposes. This will lead to minimization of the sabkha extension, mitigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…While earlier research studies on Al-Asfar and Al Uyoun lakes confirmed the presence of a wide diversity of microalgal species, their characteristics, and commercial importance, the microalgae present have never been investigated [3]. Hence, in our study, we identified and profiled, in comparison with 5 commercial algae, 168 crucial metabolites of local microalgae.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While earlier research studies on Al-Asfar and Al Uyoun lakes confirmed the presence of a wide diversity of microalgal species, their characteristics, and commercial importance, the microalgae present have never been investigated [3]. Hence, in our study, we identified and profiled, in comparison with 5 commercial algae, 168 crucial metabolites of local microalgae.…”
Section: Discussionmentioning
confidence: 88%
“…At its heart lies an extensive irrigation network with 1450 km of concrete channels, and the impressive Al-Asfar Lake, the largest evaporation lake in the country, located 13 km to the east. These artificial or natural evaporation lakes play a vital role in connecting water and land environments, providing habitat for wildlife, mitigating pollution impacts, replenishing groundwater resources, and offering flood protection [1][2][3]. Al-Asfar Lake, nestled in the Al-Ahsa region, is a natural reservoir teeming with diverse microalgae variants unique to Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The lake is characterized by a massive expanse of open water and extensive growth of flora much appears around the lake. 4,5 The lake has a shallow depth that inhibits thermal stratification where the maximum depth of the lake reaches 1.5 meters, and the water temperature of the lake follows the temperature of the surrounding air. 6 The lake water had a narrow alkaline nature pH range ranging from 7 to 8.3.…”
Section: Introductionmentioning
confidence: 99%
“…6 The lake water had a narrow alkaline nature pH range ranging from 7 to 8.3. 5 l-Asfar Lake is marked by heavy metal pollution such as copper, zinc, and cadmium which is a significant problem with wide-ranging environmental impacts including the decline in water quality and accumulation of metals in aquatic organisms' tissues. 6 This bioaccumulation can lead to high concentrations of toxic metals in the food chain, potentially affecting human health if contaminated fish are consumed.…”
Section: Introductionmentioning
confidence: 99%